Susceptibility pattern of Candida albicans isolated from Iranian patients to antifungal agents - Badiee, P (Curr Med Mycol, 2016)
BACKGROUND AND PURPOSE: Candidiasis is a major fungal infection, and Candida albicans is the major cause of infections in humans. The Clinical and Laboratory Standards Institute (CLSI) developed new breakpoints for antifungal agents against C. albicans. In this multi-center study, we aimed to determine the drug susceptibility profile of C. albicans, isolated from Iranian population according to new species-specific CLSI. MATERIALS AND METHODS: Clinical samples were cultured on Sabouraud dextrose agar and were incubated at room temperature for seven days. The isolates were transferred to Professor Alborzi Clinical Microbiology Research Center, Shiraz, Iran. C. albicans were identified by using API 20C AUX system. Broth microdilution method was used to determine the minimum inhibitory concentrations (MICs) of amphotericin B, caspofungin, voriconazole, fluconazole, posaconazole, itraconazole, and ketoconazole, based on CLSI document M27-S4 and new breakpoints for some azoles and caspofungin. RESULTS: Overall, 397 C. albicans were isolated from patients admitted to ten university hospitals in Iran. The MIC90 of the isolates to amphotericin B, caspofungin, voriconazole, fluconazole, posaconazole, itraconazole, and ketoconazole were 0.125, 0.125, 0.125, 1, 0.064, 0.5, and 0.125 µg/ml, and rates of resistance were 0.5%, 0.3%, 3.8%, 2.8%, and 2.5% for amphotericin B, caspofungin, voriconazole, fluconazole, and itraconazole, respectively. CONCLUSION: According to our data, fluconazole is the drug of choice for management of patients at risk for systemic candidiasis throughout the region, since it is cost-effective with low side effects.